Rosdiana, Mega PERSEPSI MAHASISWA SEMESTER 4 DAN DOSEN AKUNTANSI MENGENAI MATERI IFRS DI POLITEKNIK NSC SURABAYA (JBT (JURNAL BISNIS dan TEKNOLOGI), 2014)
Accounting as an information provider in the economic decision making is influenced by the business environment is constantly changing due to globalization. As of now the application of new accounting standards is IFRS ( International Financial Reporting Standards ). Following adoption of IFRS ( International Financial Reporting Standards ) in Indonesia, which has started since January 1, 2012. There are many students who don’t understand or comprehend the IFRS. Could of it happening because of several factors, is 1 ) Lack of willingness of students to read the book or IFRS of looking at the social network 2 ) Lack of support or knowledge given by the lecturers them self; 3 ) The absence of a curriculum that includes learning about IFRS. Even should all or accounting students prepare for the accounting profession to understand the existing accounting standards in Indonesia today, it's just that until now has not been all too visible. So it needs a lot of ways to do to be able to prepare their self after I graduate from college and go to business. With this method of teaching material should be adjusted to IFRS competencies to be achieved. Besides accounting education is not only the responsibility of the college. The parties that have influence on the development of accounting is appropriate join this noble task. IAI ( Indonesian Institute of Accountants ) and DSAK ( Financial Accounting Standards Board ) should be actively involved to educate the business community in the face of change and not just make a change, such as teacher certification IFRS, IFRS training, financial accounting faculty board meeting. Accounting education, at all levels, do not miss the main target of success IFRSconvergence program. Therefore, many universities are changing financial accounting curriculum to include content of IFRS and train lecturers to be ready to teach IFRS even replace text books with the issue of IFRS. However, the accounting faculty as not having enough time to at least sit down and observeIFRS react proportionately.